The secrecy of justice and the publicity of procedural and administrative acts in the Code of Civil Procedure (Research, Society and Development, 2021)
This article aims to demonstrate the exceptions to the rule of publicity of procedural and administrative acts provided for in the Code of Civil Procedure. For this purpose, it describes the hypotheses in which the secrecy of justice may be conferred on a process, noting that the hypotheses are restricted to the exhaustive list provided for the Code of Civil Procedure, as well as the analysis of the fundamental right to publicity of procedural and administrative acts, as well as its intrinsic relation with the right to access to justice, the adversary system and full defense, describing that the hypotheses of secrecy of justice do not constitute an affront to the Federal Constitution, insofar as they also aim to protect certain situations related to the right to intimacy and private life of the parties, being the reason for the aforementioned exhaustive list provided for in the civil procedural diploma. Therefore, it was concluded that using weighting criteria and the analysis of the concrete case, neither the hypothesis of secrecy of justice, nor the rule of publicity of the acts, constitutes a violation of rights. We opted for the deductive methodology, with bibliographical research in doctrine, Federal Constitution and infra-constitutional legislation.